Mencermati Isi dan Visi Undang-undang Nomor 5 Tahun 1999 tentang Anti Monopoli - Badriyah Rifa'i (Jurnal Hukum IUS QUIA IUSTUM, 2001)
Monopoly is a problem of business and trade in the world. The effect of monopoly causes: the price determination with an inclination to produce ineffecien source alloca tion and to make the higherpace than the normal one. How to manage arrangement and behaviour for market players orderly, justice and profitable in order that continous busi ness activities can develop. This article is going to accurafe vision and mission ofantimonopolyrules number 5in the year of1999.